Dynamics of magnetic flux tubes and IR-variability of young stellar objects. (August 2018) - Khaibrakhmanov, Sergey; Dudorov, Alexander; Sobolev, Andrey
Abstract: We simulate the dynamics of slender magnetic flux tubes (MFTs) in the accretion disks of T Tauri stars. The dynamical equations of our model take into account aerodynamic and turbulent drag forces, and the radiative heat exchange between the MFT and ambient gas. The structure of the disk is calculated with the help of our MHD model of the accretion disks. We consider the MFTs formed at distances of 0.027−0.8 au from the star with various initial radii and plasma betas β 0 . The simulations show that MFTs with a weak magnetic field ( β 0 = 10) rise slowly with speeds less than the speed of sound. MFTs with β 0 = 1 form an outflowing magnetized corona above the disk. Strongly magnetized MFTs ( β 0 = 0.1) can cause outflows with velocities 20 – 50 km s −1 . The tubes rise periodically over times from several days to several months according to our simulations. We propose that periodically rising MFTs can absorb stellar radiation and contribute to the IR-variability of young stellar objects.